Primary Squamous Cell Carcinoma of Submandibular Salivary Gland with Sialo-Cutaneous Fistula: A Rare Case Report - Kulkarni, Aditya Atul (J Clin Diagn Res, 2015)
Malignant tumours of the submandibular salivary glands are rare entities. Most common malignant tumour of submandibular gland is mucoepidermoid carcinoma. Histological finding of squamous cell carcinoma is very rare in submandibular salivary gland. Metastasis from distant primary squamous malignancy, direct invasion from cutaneous or mucosal squamous carcinoma, squamous component of mucoepidermoid carcinoma or primary squamous cell carcinoma of salivary origin are some of the possible causes. Of these, the latter is distinctly uncommon. Primary squamous malignancy is diagnosed only after ruling out other possible explanations. A positive mucin stain in the tumour or synchronous/ metachronous squamous carcinoma elsewhere excludes the diagnosis of a primary carcinoma. Primary squamous carcinoma is seen most commonly in parotid gland and rarely in submandibular gland. We present a case of primary squamous cell carcinoma of right submandibular salivary gland in a 45-year old-man. This case is presented for the rare entity of primary squamous cell carcinoma in submandibular salivary gland.